Artificial Intelligence (AI) in early childhood education: Curriculum design and future directions - Su, Jiahong; Zhong, Yuchun (Computers and education. Artificial intelligence, 2022)
With the rapid technological development of society brought on by Artificial Intelligence (AI), the demand for AI-literate workers will increase in the future. It is critical to develop the next generation's AI competencies and educate them about how to work with and use AI. Previous studies on AI were predominantly focused on secondary and university education; however, research on the Artificial Intelligence curriculum in early childhood education is scarce. Due to the lack of conformity on the standardisation of AI curriculum for early childhood education, this study examines the AI curriculum for kindergarten children using the framework which consists of four key components, including (1) aims, goals, objectives, or declarations of outcome, (2) subject matter, domains, or content, (3) methods or procedure, (4) evaluation and assessment. We recommend that AI literacy be achieved by three competencies: AI Knowledge, AI Skill, and AI Attitude. The employment of a social robot as a learning companion and programmable artifact was proven to be helpful in assisting young children in grasping AI principles. We also discovered which teaching methods had the most greatest influence on students' learning. We recommend problem-based learning for future AI education based on the findings.